FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGOBATAN MASAL DI KELURAHAN NON ENDEMIS FILARIASIS KOTA PEKALONGAN - Nurlaila Nurlaila; Praba Ginandjar; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Filariasis is disease that caused by filaria worm. Mass Drug Administration is a program to eliminate filariasis. Pekalongan City had started MDA in 2011. Yet Transmission Assessment Survey showed mf rate in 2015 remained exceed the threshold (1%). As a result, Pekalongan City still have to continue MDA. The latest research in Pekalongan Regency showed that compliance subject in taking MDA was lower in non endemic villages. This study aimed to analyze factors associated with MDA compliance in non endemic villages of filariasis according to Health Belief Model theory. This research used rapid survey with cross sectional approach. There was two stages sampling. First stage was 25 cluster selected randomly based on PPS using Csurvey application. Second stage was 10 subjects from each cluster randomly selescted by simple random sampling. Total sample consist of 250 respondents. Data obtained by structured interviews using questionnaires. Data was analyzed using chi square. The results showed that the compliance subject in non endemic villages was 66.8%. Education (p=0.024), knowledge of filariasis (0.049), perceived severity (p=0.000), perceived benefit (p=0.000), perceived barrier (p=0.000), internal cues to action (p=0.000), external cues to action (p=0.000), place of getting information (p=0.018), and elimination officer support (p=0.001) were significantly related to MDA compliance. The awareness of the disease, health-illness perception, and side effect were dominant factors of non compliance in taking MDA. Further, MDA information and community empowerment were needed to improve MDA compliance, beside training for Elimination Officer was needed to improve the performance of supervision.